Інформаційно-рекомендаційна система з урахуванням історії вибору користувача - Іванов, М. Д.; Іванов, В. Г. (ХНУРЕ, 2025)
Modern e-commerce is rapidly evolving, providing businesses wІТh automated solutions for managing sales and customer interactions. Wholesale trading requires effective tools for order management and personalized recommendations. This study proposes a service-oriented archІТecture (SOA) approach for developing an intelligent wholesale e-commerce system that incorporates automated product recommendations. The system optimizes product selection, streamlines order processing, and enhances business efficiency. By leveraging ASP.NET Core, SQL Server, the proposed solution improves customer experience and supports scalable business operations.
Keywords: e-commerce; рекомендаційна система